2008
DOI: 10.1002/lsm.20686
|View full text |Cite
|
Sign up to set email alerts
|

Photodynamic therapy of cervical intraepithelial neoplasia with hexaminolevulinate

Abstract: HAL PDT seems to be a non-invasive, repeatable procedure for CIN and cervical HPV infection with minimal side effects which can be easily performed on outpatient basis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
36
2
4

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 74 publications
(43 citation statements)
references
References 31 publications
1
36
2
4
Order By: Relevance
“…Three months after photodynamic therapy, there were no signs of CIN lesions in only 33% of the patients, in 42% there was no change in the CIN grade and in 25% there was an apparent progression of the disease [26]. In contrast, Soergel et al [27] reported on a remission rate of 50-70% using hexaminolevulinate as a photosensitizer (see also Hillemanns et al: ''Fluorescence diagnosis and photodynamic therapy for lower genital tract diseases -A review'' in this issue).…”
Section: Article In Pressmentioning
confidence: 75%
“…Three months after photodynamic therapy, there were no signs of CIN lesions in only 33% of the patients, in 42% there was no change in the CIN grade and in 25% there was an apparent progression of the disease [26]. In contrast, Soergel et al [27] reported on a remission rate of 50-70% using hexaminolevulinate as a photosensitizer (see also Hillemanns et al: ''Fluorescence diagnosis and photodynamic therapy for lower genital tract diseases -A review'' in this issue).…”
Section: Article In Pressmentioning
confidence: 75%
“…Both studies described high epithelial fluorescence and a significant selectivity between epithelium and underlying lamina propria [15,16]. In a first pilot study, the feasibility of HAL-PDT was evaluated in 24 patients with a CIN 2 or 3 or a persistent CIN 1 and a positive high-risk HPV-DNA test [17]. Each patient had a gynecological examination including cervical cytology, HPV-DNA testing, colposcopy and biopsy.…”
Section: Photodynamic Therapy Of Cin 1-3mentioning
confidence: 99%
“…ALA is applied topically as a prodrug of PpIX, serving as a sensitizer used in photodynamic therapy (PDT) to treat special skin tumours or cancer of the bladder, oesophagus, lung and cervix (Berger et al, 2003;Blume and Oseroff, 2007;Soergel et al, 2008). The accumulation of PpIX following ALA administration is more pronounced in malignant cells compared with their normal counterparts in vitro and in vivo.…”
Section: Introductionmentioning
confidence: 99%